2007
DOI: 10.2169/internalmedicine.46.0117
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Acute Exacerbation of Interstitial Pneumonia Treated with Polymyxin B-immobilized Fiber Column Hemoperfusion Treatment

Abstract: The effect of polymixin B-immobilized fiber column (PMX)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Five ventilated patients were weaned from the ventilation at one point. Our findings are consistent with other reports that have described the effectiveness of PMX-DHP for patients with AE-IP [18,19,21]. In addition to our assessment of oxygenation, we also assessed the systemic effect of PMX-DHP on rapidly progressive IP.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Five ventilated patients were weaned from the ventilation at one point. Our findings are consistent with other reports that have described the effectiveness of PMX-DHP for patients with AE-IP [18,19,21]. In addition to our assessment of oxygenation, we also assessed the systemic effect of PMX-DHP on rapidly progressive IP.…”
Section: Discussionsupporting
confidence: 89%
“…Other scoring systems could be useful to assess patients with IP; for example, the RIFLE score predicts the outcome of ARDS patients who undergo open lung biopsy [37]. The mortality rates for patients with rapidly progressive IP in 3 recent reports [18,19,21] were 33.3, 50 and 60%, respectively. The 30-day mortality rate in the present study was 36.3%, and the 90-day mortality rate was 51.6%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although immunosuppressive therapy with cyclosporin A (CyA) (7,10) and polymyxin B-immobilized fiber column hemoperfusion treatment (18) has been reported to be effective to some extent, a sufficiently effective therapy has not yet been established. Some investigators even reported the sterility of intensive care unit and a ventilator for patients with AE-IPF, because the mortality of these patients approaches 100% (9,11,16,19).…”
Section: Introductionmentioning
confidence: 99%